REKONTRUKSI KARAKTERISTIK BUDAYA ORGANISASI DI INDONESIA DALAM MENINGKATKAN KOMPETENSI SUMBER DAYA MANUSIA - Mulyaningsih Mulyaningsih (Jurnal Ilmiah P2M STKIP Siliwangi, 2020)
Human resources must be used as thoughts towards changing attitudes and views of the nation as a consequence of humans as individuals in their relations with the national and international community. Strategically Characteristics of Organizational Culture owned by Indonesian HR must be able to support the implementation of development progress through measurable capabilities by having organized entrepreneurial capacity that makes Indonesian HR a 'model of sharing' and agents of change from the reconstruction of values. the value contained in Pancasila as a noble value of the positive character possessed by the Indonesian people through the results of research studies at the Sundanese level, namely: "Sarendek Saigeul Sabobot Sapihanean, Parahyuhan sahan, simbeuh and identity, Involvement; participate actively, consistency is to carry out the mission; work synchronization, level of creativity. With the thought of sharing is a good attitude or action that has been present among Indonesian community organizations, including the smallest membership of Indonesian society, namely the family. Cultural characteristics of the Indonesian HR organization are tools for educator experts or those who pay attention to education, human resource development planners and entrepreneurs to make the right decisions in HR management policies that consistently utilize HR potential in building patterns to counteract the nation's problems, especially in dealing with ASIAN Future Shock in 2020 with the method of cultural approach as an image of the nation on an ongoing basis towards improving the quality of the nation in the national policy circle